Facial Artery Perforator and Depressor Anguli Oris Muscle Chimeric Flap: A New Design of an Old Flap. Issue 2 (August 2016) - Sarici, Murat; Yeşiloğlu, Nebil; Temiz, Gökhan; Şirinoğlu, Hakan; Güvercin, Emre; Filinte, Gaye Taylan
Abstract : Background: The aim of this study was to investigate the reliability and outcomes of the facial artery perforator and separately elevated depressor anguli oris (DAO) muscle chimeric flap for the reconstruction of partial or total lower lip defects. Methods: Eleven patients with malignant skin tumors located at the lower lip were operated between 2013 and 2015. After the excision of the tumor with adequate clear margins using margin controlled excision technique, an appropriate flap fitting to the resultant defect based on the perforators of the facial artery and DAO muscle was prepared and placed into the defect. The DAO muscle activity was tested with electromyography in the postoperative first year examination. Results: Besides 1 patient with transient venous insufficiency, all the flaps healed well without a partial or total flap loss. The mean follow-up period was 10 months. No new primary tumor or recurrence was observed. Although in 1 patient, transient asymmetric smiling and mild drooling was observed, the overall oral competence results were found to be quite satisfactory. The electromyography evaluation of DAO muscle of 5 patients who reached the postoperative first year examination showed action potential results in normal limits with a slight decrease. All patients were satisfied with the final esthetic and functional result. Conclusions: The facial artery perforator and depressor angel oris muscle chimeric flap is a valuable option for reconstruction of lower lip defects providing esthetically and functionally good results.